Variation in pasting and functional properties of flours and starches from water yam (Dioscorea alata) - Oke, M.O.; Awonorin, S.O.; Asiedu, Robert; Maziya-Dixon, B.B.; Sanni, Lateef O.; Akinwande, B.A. (2009)
This study was carried out in order to compare pasting behavior and functional characteristics of flours and starches from ten varieties of water yam (D. alata). Differences were established among the arieties in the functional and physical properties of the starches and flours, including swelling power, solubility index, and water absorption capacity. The swelling power of the water yam flour and starch put them in the category of highly restricted swelling starch. This characteristic is desirable for the manufacture of value-added products such as noodles and composite blends with cereals. The uses of starch from improved yam varieties to impart viscosity to locally processed foods have remarkable potential in Africa.